Key thinkers from critical theory to post-Marxism - Tormey, Simon, 1963-; Townshend, Jules, 1945-; Sage eBooks (London : SAGE, 2006)
This volume is a comprehensive introduction to the most key intellectual trend in contemporary critical theory. In jargon-free language it seeks to unpack, explain and review many of the key figures behind the rethinking of the legacy of Marxism in theory and practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Political science -- Philosophy; Philosophers, Modern; Critical theory; Philosophy, Marxist; Electronic books